PENGARUH REFORMASI EKONOMI INDIA MENGENAI FOREIGN DIRECT INVESTMENT (FDI) TERHADAP STRATEGI INVESTASI SOFTBANK GROUP CORPORATION DI INDIA2013-2016 - Sumbari, Titi; Harto, Syafri (Fakultas Ilmu Sosial dan Ilmu Politik Universitas Riau, 2017)
This research analyze about the impact of economic reforms in India regarding foreign direct investment (FDI) toward Softbank Group Corporation’s investment strategy in India in 2013-2016. The economic reforms undertaken by the India government on FDI provides an opportunity for Softbank Group Corporation to invest in India. The investment is poured on telecommunications and internet sector in India through the provision of capital to startup and e-commerce firms in India. In addition investment is also given to the renewable energy sector in India by setting up a joint venture.The writer collects data from journals, books, reports, working papers, tabloids, and online media to analyze the research. The theoretical framework applied in this research are neoliberalism perspective, foreign policy theory from K.J Holsti, and foreign direct investment theory from Jhon Dunning.The research shows that the impact of economic reform in India regarding foreign direct investment (FDI) toward Softbank Group Corporation’s investment strategy in India is increasing the number of Softbank investment in India, which is both the telecommunications and internet sector and the renewable energy sector in India. In his ambitions, Softbank Group Corporation committed to invest big in these two sectors in the next decade.Kata Kunci: reform, foreign direct investment, Softbank Group Corporation, stratup, e-commerce, renewable energy, joint venture